Prevalence and Factors Associated with Lower Reproductive Tract Infections Among Married Women Aged 18–49 in Dong Phu Commune, Long Ho District, Vinh Long Province, 2018 - Nguyen Thi Ngoc, Bich; Doan Thi Thuy, Duong; EVansluong David Vinh, Quang (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2020)
Objective: To understand the patterns and associated factors of reproductive tract infections among married women aged from 18 to 49 in Dong Phu Commune, Long Ho District, Vinh Long Province in 2018.Methods: A cross-sectional study was conducted with 420 married women aged 18-49 by systematic sampling. Participants were invited to have a gynecological examination and answer a questionnaire at Dong Phu commune health station.Results: Of 420 women, 43.6% had lower reproductive tract infections, and those who had bacterial vaginosis accounted for 36.2%, vaginal candidiasis accounted for 9.3%, and Trichomonas vaginalis accounted for 1.0%. Factors associated with lower reproductive tract infections, including occupation, abortion history, and adherence to treatment, were found in this study.Conclusion: The prevalence of genital tract infections (by one of three types) is 43.6%. It is necessary to enhance counseling services and behavior change communication for women who work as peasants, gardeners, fisherwomen, housewives; and to improve the quality of abortion services and the awareness of treatment adherence.
Keywords: lower reproductive tract infections; women; Vinh Long.